Evaluation of feasibility and utility of urinary lipoarabinomannan assay against conventional sputum microscopy in the detection of tuberculosis among people with and without HIV infection - Chakrapani Chatla; Neetu Mishra; Malathi Jojula; Vijay Nema; Rajesham Adepu; Mallikarjun Puttala (Clinical Epidemiology and Global Health)
Background: Tuberculosis (TB) is a major global public health challenge. Lipoarabinomannan (LAM) assessment in urine is a potential molecular diagnostic tool for TB. Methods: We evaluated the feasibility and utility of urinary LAM in detecting TB along with sputum smear microscopy (SSM) and the TrueNAT test. In an observational cross-sectional pilot study, we collected sputum and urine samples from 240 subjects visiting the Designated Microscopy Center, Warangal during Apr-Sep 2021. LED microscopy, TrueNAT and liquid culture were performed on sputum while LAM test was conducted on urine samples. Results: Mean age of the subjects was 45.1 (SD = 16.1) years. The majority were men (66 %), married (89 %) and urban (52 %) subjects. Overall sensitivity of urine LAM was 63.6 % and specificity 80.1 % while that of LED microscopy were 59.6 % and 56.7 % respectively. TrueNAT had sensitivity of 58.6 % and specificity of 80.1 %. However, a combination of LAM + TrueNAT had 79.8 % sensitivity. Among PLHIV, LAM + SSM has better sensitivity than any other combination of these tests or alone across all CD4 count categories. Conclusion: Urinary LAM can be a more useful, feasible and better TB diagnostic biomarker over LED microscopy in diagnosing TB among the subjects who have symptoms irrespective of HIV status and recommend further evaluation of next-generation urinary LAM diagnostics to reach the unreached through a point of care tool.